Analysis of the Impact of University Accounting Education on Micro Companies. Anecuadorian case - Cuamacás, Gloria Esperanza Aragón; Paredes, Virna Isabel Acosta; Medina, Helen Magdalena Gómez; González, Luz Marina Pereira; Moya, Camilo Rigoberto Campaña; Aragón, María Piedad Ortega (Journal of international crisis and risk communication research (Print), 2024)
The present study of the Research Project: "Analysis of University Accounting Education for Microenterprises in Ibarra" carried out by the Technical del Norte University, allowed to analyze the impact of accounting education with contribution for small companies in the sector, because higher education establishments need advance and innovate accounting academic management, with teaching and student attention, for practical support, in tune with the reality of the organizational environment. The type of exploratory, descriptive methodology, with the use of the statistical method, applied probabilistic sampling and the census, to examine 40 microenterprises and 83 accounting specialization university students; Once the diagnosis was applied, the information was classified and two databases were entered into the SPSS program for statistical analysis. The results were satisfactory, finding Cronbach's Alpha with a reliability level of (0.850) for microenterprises and (0.810) for students, which agrees with the effect of correlation and application of Varimax orthogonal rotation, reflecting the accounting training tax; Thus, the impact of medium-high accounting education was determined, with (40%) and (25%) micro-enterprise satisfaction and medium-high support of (28%) and (58%) of student reception. Finally, it was reflected that the results of the study raise awareness of the high responsibility towards continuous innovation in academic processes, facilitating the accounting culture for small companies, with sustainability and applicability of educational strategies for relevant financial accounting management, according to current trends in the economic and social context.